Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Toko Genre.Catalog Kota Depok - Raju Ardiansyah, Ahmad; Rahayu, Surhani (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. The purpose of this research is to determine the Price Variable (X1), Product Quality (X2), Purchasing Decision (Y), and the Influence of Price and Product Quality on Purchasing Decision Consumer at Toko Genre.Catalog. This research method uses a quantitative method with an quantitative descriptive approach and the population in this research is 3.752 consumers. The sample used in this research used the entire population of 97 consumers as respondents. In this research the sampling technique used is probabiblity sampling. The result of Price variabel have a significant effect on Purchasing Decision with tcount value of 10,485 > ttabel value of 1,986 and a Sig.< 0,05 (0,000 < 0,05). The result of Product Quality variabel have a significant effect on Purchasing Decision with tcount value of 3,509 > ttabel value of 1,986 and a Sig. < 0,05 (0,000 < 0,05). The result of The Price and Product Quality variable simultaneously have a significant influence on Purchasing Decision with calculated fvalue of 68,189 > 3,09 and a Sig. value < 0,05 (0,000 < 0,05). Keywords: Price, Product Quality, Purchasing Decision